PENGARUH KECERDASAN EMOSIONAL (EQ) DAN KECERDASAN SPIRITUAL (SQ) TERHADAP KINERJA KARYAWAN DI PT. NARENDRA DEWA YOGA KOTA BENGKULU - Rio Pentydia (IAIN Bengkulu, 2018)
The purpose of writing this thesis is (1) To describe whether there is a significant and positive influence between emo- tional intelligence (EQ) variable to employee performance variable at PT. Narendra God of Yoga. (2) To describe whether there is a significant and positive influence between the variables of spiritual intelligence (SQ) on employee performance variables in PT. Narendra God of Yoga. (3) To describe whether there is a significant and positive influence between emotional intelligence (EQ) and Spiritual Intelligence (SQ) variable to employee performance variable in PT. Narendra God of Yoga. The method used in this research is descriptive quantitative research method, furthermore, the analysis technique using simple linear regression and multiple linear regression, F test and double correlation with the help of computer program SPSS Version 16.0. The results of this study indicate that together there is a significant influence between emotional intelligence (EQ) and spiritual intelligence (SQ) variable to employee performance variable at PT. Narendra God of Yoga